The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1155/2013/290568
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Breast Cancer Recurrence

Abstract: Breast cancer remains a deadly disease, even with all the recent technological advancements. Early intervention has made an impact, but an overwhelmingly large number of breast cancer patients still live under the fear of “recurrent” disease. Breast cancer recurrence is clinically a huge problem and one that is largely not well understood. Over the years, a number of factors have been studied with an overarching aim of being able to prognose recurrent disease. This paper attempts to provide an overview of our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
100
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(110 citation statements)
references
References 187 publications
0
100
1
1
Order By: Relevance
“…Although the employment of screening programs and the development of new therapeutics for breast cancer have significantly reduced mortality rates in the Western world, tumour resistance to these therapeutics is a growing problem (Ahmad 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although the employment of screening programs and the development of new therapeutics for breast cancer have significantly reduced mortality rates in the Western world, tumour resistance to these therapeutics is a growing problem (Ahmad 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, drug resistance still remains a puzzling problem which has been an obstacle to the clinical treatment of breast cancer [4]. Research showed that 30% of the patients with early stage breast cancer relapsed and developed metastatic disease, at least a quarter of which were the results of resistance to the therapeutic agents [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although a few screening tools exist to determine who is at risk of recurrence, overall the molecular dynamics are still poorly understood [6]. It is also well described in the literature that angiogenesis plays an important role in hormonal resistance and further tumor recurrence in cases of previously treated breast carcinoma [7] [8] [9] [10] [11].…”
mentioning
confidence: 99%